Inactivation of Staphylococcal Phenol Soluble Modulins by Serum Lipoprotein Particles - Surewaard, Bas G. J. (Public Library of Science, 2012)
Staphylococcus aureus virulence has been associated with the production of phenol soluble modulins (PSM). PSM are known to activate, attract and lyse neutrophils. However, the functional characterizations were generally performed in the absence of human serum. Here, we demonstrate that human serum can inhibit all the previously-described activities of PSM. We observed that serum can fully block both the cell lysis and FPR2 activation of neutrophils. We show a direct interaction between PSM and serum lipoproteins in human serum and whole blood. Subsequent analysis using purified high, low, and very low density lipoproteins (HDL, LDL, and VLDL) revealed that they indeed neutralize PSM. The lipoprotein HDL showed highest binding and antagonizing capacity for PSM. Furthermore, we show potential intracellular production of PSM by S. aureus upon phagocytosis by neutrophils, which opens a new area for exploration of the intracellular lytic capacity of PSM. Collectively, our data show that in a serum environment the function of PSM as important extracellular toxins should be reconsidered.